Rayleigh wave constraints on the structure and tectonic history of the Gamburtsev Subglacial Mountains, East Antarctica. Issue 5 (10th May 2013) - Heeszel, David S.; Wiens, Douglas A.; Nyblade, Andrew A.; Hansen, Samantha E.; Kanao, Masaki; An, Meijan; Zhao, Yue
Abstract : [1] The Gamburtsev Subglacial Mountains (GSM), located near the center of East Antarctica, remain one of the most enigmatic mountain ranges on Earth. A lack of direct geologic samples renders their tectonic history almost totally unconstrained. We utilize teleseismic Rayleigh wave data from a 2 year deployment of broadband seismic stations across the region to image shear velocity structure and analyze the lithospheric age of the GSM and surrounding regions. We solve for 2‐D phase velocities and invert these results for 3‐D shear velocity structure. We perform a Monte Carlo simulation to improve constraints of crustal thickness and shear velocity structure. Beneath the core of the GSM, we find crustal thickness in excess of 55 km. Mantle shear velocities remain faster than global average models to a depth of approximately 250 km, indicating a thick lithospheric root. Thinner crust and slower upper mantle velocities are observed beneath the Lambert Rift System and the Polar Subglacial Basin. When compared with phase velocity curves corresponding to specific tectonothermal ages elsewhere in the world, average phase velocity results for the GSM are consistent with regions of Archean‐Paleoproterozoic origin. Combined with radiometric ages of detrital zircons found offshore, these results indicate a region of old crust that has undergone repeated periods of uplift and erosion, most recently during the Mesozoic breakup of Gondwana. Lower crustal seismic velocities imply a moderately dense lower crust beneath the core of the GSM, but with lower density than suggested by recent gravity models. Key Points: Gamburtsev Subglacial Mountains underlain by thick lithosphere Lithospheric structure consistent with Archean - Mesoproterozoic age globally Repeated periods up uplift and erosion the last during the Mesozoic